Absolute microvascular resistance by continuous thermodilution predicts microvascular dysfunction after ST-elevation myocardial infarction. (15th November 2020) - Konstantinou, Klio; Karamasis, Grigoris V.; Davies, John R.; Alsanjari, Osama; Tang, Kare H.; Gamma, Reto A.; Kelly, Paul R.; Pijls, Nico H.J.; Keeble, Thomas R.; Clesham, Gerald J.
Abstract: Aims: Continuous thermodilution using intracoronary saline infusion is a novel technique able to provide accurate measurements of absolute coronary blood flow and microvascular resistance (Rmicro ). The aim of this study was to assess the ability of Rmicro, measured by continuous thermodilution, to predict microvascular dysfunction in patients with ST-elevation myocardial infarction. Methods and results: In this prospective observational study, continuous thermodilution was used to measure Rmicro in the culprit coronary artery of 32 patients with STEMI (mean age ± SD, 66 ± 10 years; 78% male) immediately post-primary percutaneous coronary intervention (PCI). Concomitant measurements of the index of microvascular resistance (IMR) and coronary flow reserve (CFR) were obtained by bolus thermodilution. Microvascular dysfunction was defined as an IMR > 40 or a CFR < 2. Rmicro was higher in patients with microvascular dysfunction based on the predefined thresholds; for IMR: 863 (IQR, 521–1079) vs 474 (IQR, 337–616) Wood units, p  = .004 and for CFR: 633 (IQR, 455–1039) vs 474 (IQR, 271–579) Wood units, p  = .02. Receiver-operator characteristic analysis demonstrated that Rmicro was predictive of microvascular dysfunction; area under curve (AUC) 0.800 (95% CI: 0.637–0.963, p  = .005) for IMR-defined microvascular dysfunction and AUC 0.758 (95% CI: 0.593–0.924, p  = .02) for CFR-defined microvascular dysfunction. An Rmicro threshold of greater than 552 Wood units was optimal for predicting microvascular dysfunction defined by IMR > 40. Conclusions: Rmicro is able to identify STEMI patients in whom IMR and CFR measurements suggest significant microvascular dysfunction at the end of primary PCI. Highlights: Continuous thermodilution is a novel technique that can quantify microvascular resistance (Rmicro). Our exploratory study showed that Rmicrowas predictive of microvascular dysfunction in a STEMI population. Timely assessment of microvascular dysfunction in STEMI can guide patient management. The clinical value of Rmicro should be explored in larger studies.